2017
DOI: 10.17294/2330-0698.1415
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma Vaccination Patterns in a Large Health System: A Pilot Study

Abstract: Journal of Patient-Centered Research and Reviews ( JPCRR) is a peerreviewed scientific journal whose mission is to communicate clinical and bench research findings, with the goal of improving the quality of human health, the care of the individual patient, and the care of populations. Recommended CitationAlemu A, Singh M, Blumberg C, Richards JO, Oaks MK, Thompson MA. Multiple myeloma vaccination patterns in a large health system: a pilot study. J Patient Cent Res Rev. 2017;4:53-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Patients’ compliance with their physicians’ advice was remarkably high with good compliance rates (greater than 80%) for influenza, pneumococci, hepatitis B, and DTP. The rates of recommendations for influenza and pneumococci were higher than reported in a previous study for US myeloma patients 4 and supported by clinical experience and data showing that upper and lower respiratory tract infections are the most frequently observed infectious complications in patients with MM. 1 Upper respiratory tract infections disturb the complex equilibrium between commensal bacteria and viruses and facilitate the development of lower respiratory tract bacterial and viral infections, 5 underlining the need for applying the available prevention strategies.…”
supporting
confidence: 75%
“…Patients’ compliance with their physicians’ advice was remarkably high with good compliance rates (greater than 80%) for influenza, pneumococci, hepatitis B, and DTP. The rates of recommendations for influenza and pneumococci were higher than reported in a previous study for US myeloma patients 4 and supported by clinical experience and data showing that upper and lower respiratory tract infections are the most frequently observed infectious complications in patients with MM. 1 Upper respiratory tract infections disturb the complex equilibrium between commensal bacteria and viruses and facilitate the development of lower respiratory tract bacterial and viral infections, 5 underlining the need for applying the available prevention strategies.…”
supporting
confidence: 75%
“…Infections remain the most common cause of morbidity and mortality in multiple myeloma besides the disease itself [ 1 , 2 ]. The risk of infection is increased already at the stage of MGUS [ 3 ], and is even higher in patients with active disease when starting anti-myeloma therapy.…”
Section: Introductionmentioning
confidence: 99%
“…One small retrospective American study with 411 MM patients from 2012 to 2014 found that 58% had received at least one SP vaccine [ 28 ]. To our knowledge, this is the only other study of vaccination rates in MM patients.…”
Section: Discussionmentioning
confidence: 99%